Perbandingan PEG, α-CD, dan SLS dalam Preparasi Serum Lipemik pada Pemeriksaan AST - Nurhaliza, Siti; Riyani, Ani; Nurhayati, Dewi; Kurnaeni, Nani (JPP JURNAL KESEHATAN POLTEKKES PALEMBANG, 2025)
Background: Lipemic serum can interfere with AST testing, resulting in falsely elevated values. The addition of alpha-cyclodextrin (α-CD), polyethylene glycol (PEG), and sodium lauryl sulfate (SLS) can bind to fats in lipemic serum, thereby clarifying the serum. This study aims to compare the activity of AST enzyme in pooled serum with pooled lipemic serum after adding PEG 1.5%, α-CD 1.5%, and SLS 5%, as well as the differences in AST enzyme activity between pooled lipemic serum supplemented with PEG 1.5%, α-CD 1.5%, and SLS 5%. Method: Experimental, by preparing lipemic serum using egg yolk to achieve a triglyceride level of 1500.8 mg/dL, then treated with PEG 1.5%, α-CD 1.5%, and SLS 5%, incubated for 30 minutes at 4°C, centrifuged at 3000 rpm for 10 minutes, and the AST enzyme activity was measured using the Kinetic-IFCC method and compared with pooled serum. Results: The ANOVA test results showed a significant difference in AST enzyme activity between pooled serum samples and untreated lipemic serum. However, when lipemic serum was treated with PEG 1.5%, α-CD 1.5%, and SLS 5%, no significant difference was observed compared to pooled serum. Additionally, there was no significant difference in AST enzyme activity between lipemic serum supplemented with PEG 1.5%, α-CD 1.5%, and SLS 5%. Conclusion: These three flocculants can be used to treat lipemic serum to obtain more accurate AST activity test results.